Rigid body rotation surrounding the crack - Bhattacharya A.; Kishor B. (My University, 2025)
An analysis of the rigid body rotation is presented which is based on the conventional Westergaard function and the stress function in complex form. The crack opening displacement is obtained on the basis of rotation at points lying on the crack edge. Using an expression of rotation near the crack tip the rotation at the Dugdale's crack tip plastic zone is shown to be a material constant. With the help of an analysis of rotation for the elastic region, the distribution of rotation in cracked plates having finite width are obtained. © 1988.